THE OBJECTIFICATION OF WOMEN IN KELLY SUE DECONNICK’S GRAPHIC NOVEL BITCH PLANET - Candra, Afri; Sari, Dian Eka (LINGUA LITERA : journal of english linguistics and literature, 2024)
This research investigates a dystopian graphic novel written by Kelly Sue Deconnick. It portrays women as objects and forms of women's objectification in a male-dominated world. It utilizes Simone de Beauvoir's concepts of objectivity and subjectivity to explore the position of women as objects in several areas, including private and social life. The research was qualitative. The data was collected from the literary work itself as well as other scientific articles and literature analyses. The findings showed two forms of objectification done toward women, including isolation and oppression to punish and correct their behavior. This study highlights how these themes mirror real-world gender dynamics, fostering a critical dialogue about systemic patriarchy. The graphic novel serves as a powerful medium to question and challenge societal norms regarding women's roles and identities.